2015
DOI: 10.1007/s11244-015-0472-z
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic Oxidation of Veratryl Alcohol to Veratraldehyde with Heterogeneous Ruthenium Catalysts

Abstract: Lignin is a complex polymeric molecule constituting various linkages between aromatic moieties.Typically, the -O-4 linkage accounts for more than half of the linkage structures present in lignin.The present study focuses on the oxidative transformation of veratryl alcohol (VA) -a compound Prolonged reaction time led to significant formation of the decarbonylated product veratrol from VAld. When the reaction was completed under 20 bars of argon in methanol instead of water, the methyl ether of VA (i.e. 1,2-dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Additionally, catalytic upgrading of biomass and derived compounds have been reported over various supported ruthenium oxide catalysts. 16,[36][37][38][39][40][41][42] The many applications of ruthenium in catalysis has rendered it a very wellstudied metal in both homogeneous and heterogeneous systems. [43][44][45][46][47][48][49][50][51][52][53][54] More recently, Mizuno and Yamaguchi reported high activity of supported ruthenium hydroxide catalysts (Ru(OH)x/support) in liquid-phase oxidations of alcohols, aldehydes and amines.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, catalytic upgrading of biomass and derived compounds have been reported over various supported ruthenium oxide catalysts. 16,[36][37][38][39][40][41][42] The many applications of ruthenium in catalysis has rendered it a very wellstudied metal in both homogeneous and heterogeneous systems. [43][44][45][46][47][48][49][50][51][52][53][54] More recently, Mizuno and Yamaguchi reported high activity of supported ruthenium hydroxide catalysts (Ru(OH)x/support) in liquid-phase oxidations of alcohols, aldehydes and amines.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, heterogeneous catalysts have gained a lot of interest due to their excellent performance, stability, and reusability in selective oxidation under mild conditions, and especially in the oxidation of biomass-derived substrates [ 11 ]. In the literature, studies on heterogeneous catalysts for the oxidation of veratryl alcohol have focused mainly on monometallic catalysts [ 5 ], such as Co 3 O 4 [ 9 ], Co-ZIF-9 [ 12 ], Mn/Al 2 O 3 , Co/Al 2 O 3 , Cu/Al 2 O 3 , Ag/Al 2 O 3 , Ru/Al 2 O 3 and so on [ 13 ]. Bimetallic catalysts containing Au-Pd and Au-Pt have exhibited better catalytic performance and higher stability [ 14 ] than monometallic catalysts for the selective oxidation of alcohols [ 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Homogeneous catalysts are disadvantageous, requiring multistep synthesis, often showing fast deactivation and being difficult to recover. For this reason, many researchers investigated the catalytic oxidation on biomass model compounds by heterogeneous catalysis; in fact, the catalytic oxidation of veratryl alcohol by heterogeneous catalysts has already been reported [10,11]. Nevertheless, high conversions and selectivity were obtained only under harsh reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Rode et al [10] reported the aqueous phase catalytic oxidation of veratryl alcohol by a nano-structured Co 3 O 4 catalyst, showing a conversion of 85% with 96% selectivity to veratrylaldehyde, where the reaction was carried out at 140 • C and 40 bar of O 2 . Moreover, the preparation of the catalyst required continuous stirring for 12 h at 70 • C and a calcination step at 300 • C for 5 h. Riisager et al [11] reported the oxidative transformation of VA to veratrylaldehyde (VAld) with air, by Ru supported on γ-alumina or silica: also in this case, the reaction conditions used were harsh, i.e., temperature above 150 • C and pressure higher than 3 bar. Additionally, the catalysts needed to be calcined at 450 • C for 6 h.…”
Section: Introductionmentioning
confidence: 99%